Gender Differences in Service Use in a Sample of People with Schizophrenia and Other Psychoses. (3rd April 2012) - Iniesta, Raquel; Ochoa, Susana; Usall, Judith
Abstract : Objective . The main objective is to analyze the use of mental health services in a sample of people with schizophrenia and other psychoses according to gender. Method . The sample of this observational and retrospective study (n = 7483 ) consisted of all the persons who visited any mental health service of the Parc Sanitari Sant Joan de Déu from 2001 to 2007 with a diagnosis of schizophrenia and other psychoses. The main measures analyzed regarding gender were the frequency of patients for each diagnosis, their risk of being admitted into hospital, and the number and length of hospitalizations for the subsample of inpatient people during the study period. Results . Men are more frequent in the total sample (58.1%). For diagnosis of schizoaffective or delusional disorder, women have a higher frequency than men. Women with diagnosis of schizophrenia have a lower risk of being admitted to the hospital (RR = 0.84, 95% CI (0.72, 0.97)). We found a higher risk of longer stays for men with schizophrenia of the disorganized type (RR = 0.49, 95% CI (0.30, 0.81)), undifferentiated (RR = 0.41, 95% CI (0.27, 0.61)), or delusional disorder (RR = 0.65, 95% CI (0.49, 0.87)). Conclusion . Gender of patients is a relevant variable in mental health service use by patients with schizophrenia and other psychoses.